Effect of Ti doping on the dielectric, ferroelectric and magnetic properties of Bi0.86La0.08Sm0.14FeO3 ceramics. (11th September 2019) - Gao, Rongli; Qin, Xiaofeng; Wu, Heng; Xu, Ruicheng; Liu, Lun; Wang, Zhenhua; Fu, Chunlin; Cai, Wei; Chen, Gang; Deng, Xiaoling
Abstract: By using solid states reaction method, Bi0.86 La0.08 Sm0.14 Fe1- x Ti x O3 ceramics with different Ti 4+ contents ( x  = 0, 0.01, 0.02, 0.04, 0.08, 0.12, 0.16, 0.20) were prepared. Effects of Ti doping content on the microstructure, conductive, dielectric, ferroelectric and magnetic properties were systematically studied. The Bi0.86 La0.08 Sm0.14 Fe1- x Ti x O3 perovskite structure was confirmed by XRD patterns. SEM results revealed porous and homogeneous structure of specimens. Compared with other ceramics, the sample ( x  = 0.04) shows the lowest leakage current value, which is attributed to the relatively homogeneous surface morphology and less defects. The dielectric constant increases first and then descends with increasing Ti 4+ concentration, this behavior may be caused by the existence of oxygen vacancies. The maximal dielectric constant (∼2000 at 100 Hz) is obtained in the sample ( x  = 0.16), while the specimen ( x  = 0.02) presents the largest dielectric loss (∼28, at 100 Hz). The ceramics ( x  = 0.08) shows the best ferroelectric properties, the remnant polarization ( P r ) is 1.4304 μ C/cm 2 and the coercive field ( E c ) is 25.9 kV cm −1 at the frequency of 3 kHz. The saturation magnetization ( M s ) decreases with the increase of x, because the variation of Fe 3+ can affect the domain structure. These results indicate that proper Ti 4+ doping in B site can distinctly improve the multiferroic properties of BiFeO3 based ceramics, implying potentially practical applications in electronic devices.